Cochlear Synaptic Degeneration and Regeneration After Noise: Effects of Age and Neuronal Subgroup - Hickman, Tyler T.; Hashimoto, Ken; Liberman, Leslie D.; Liberman, M. Charles (Frontiers in Cellular Neuroscience, 2021)
In CBA/CaJ mice, confocal analysis has shown that acoustic overexposure can immediately destroy synapses between auditory-nerve fibers (ANFs) and their peripheral targets, the inner hair cells (IHCs), and that years later, a corresponding number of ANF cell bodies degenerate. In guinea pig, post-exposure disappearance of pre-synaptic ribbons can be equally dramatic, however, post-exposure recovery to near-baseline counts has been reported. Since confocal counts are confounded by thresholding issues, the fall and rise of synaptic ribbon counts could represent “regeneration,” i.e. terminal retraction, re-extension and synaptogenesis, or “recovery,” i.e. down- and subsequent up-regulation of synaptic markers. To clarify, we counted pre-synaptic ribbons, assessed their juxtaposition with post-synaptic receptors, measured the extension of ANF terminals, and quantified the spatial organization and size gradients of these synaptic elements around the hair cell. Present results in guinea pigs exposed as adults (14 months), along with prior results in juveniles (1 month), suggest there is post-exposure neural regeneration in the guinea pig, but not the CBA/CaJ mouse, and that this regenerative capacity extends into adulthood. The results also show, for the first time, that the acute synaptic loss is concentrated on the modiolar side of IHCs, consistent with a selective loss of the high-threshold ANFs with low spontaneous rates. The morphological similarities between the post-exposure neurite extension and synaptogenesis, seen spontaneously in the guinea pig, and in CBA/CaJ only with forced overexpression of neurotrophins, suggest that the key difference may be in the degree of sustained or injury-induced expression of these signaling molecules in the cochlea.